Penghentian Ijtihad dan Dampaknya terhadap Pembaruan Hukum Islam di Indonesia - Wijayanti Eka Suryandari; Mustamin Giling (Al-Kindi, 2026)
The discourse surrounding the closure of the door of ijtihad has shaped Islamic legal thought for centuries, yet its historical validity and contemporary implications remain contested. This article critically examines the construction of the cessation of ijtihad both as a historical narrative and as an ongoing epistemological challenge, with particular attention to its impact on Islamic legal reform in Indonesia. Using a qualitative-normative legal research methodology grounded in historical, conceptual, and comparative approaches, this study analyzes how the narrative of stagnation emerged through the convergence of Orientalist scholarship, internal juridical developments, and the political co-optation of religious authority. This research demonstrates that Indonesia presents a unique laboratory for observing the tension between stagnation and renewal of ijtihad, characterized by the coexistence of institutionalized collective ijtihad (through the MUI and NU), progressive judicial reasoning (exemplified by the Supreme Court ruling on wajibah wills), and persistent methodological contestation between maqāṣid-oriented reform and neo-literalist pressures. The central argument of this article is that the "closed door" metaphor is historically inaccurate and theologically problematic, yet its effective power as a disciplinary mechanism continues to constrain legal innovation. The novelty of this research lies in its integrated analytical framework that synthesizes critical historiography of ijtihad, socio-legal institutional analysis, and a case study of contemporary Indonesia to propose a contextualized model of ijtihad that bridges classical methodology with modern legal challenges.